Global hotspots and emerging trends in 3D bioprinting research - Ding, Zhiyu; Tang, Ning; Huang, Junjie; Cao, Xu; Wu, Song (Frontiers in Bioengineering and Biotechnology, 2023)
Three-dimensional (3D) bioprinting is an advanced tissue engineering technique that has received a lot of interest in the past years. We aimed to highlight the characteristics of articles on 3D bioprinting, especially in terms of research hotspots and focus. Publications related to 3D bioprinting from 2007 to 2022 were acquired from the Web of Science Core Collection database. We have used VOSviewer, CiteSpace, and R-bibliometrix to perform various analyses on 3,327 published articles. The number of annual publications is increasing globally, a trend expected to continue. The United States and China were the most productive countries with the closest cooperation and the most research and development investment funds in this field. Harvard Medical School and Tsinghua University are the top-ranked institutions in the United States and China, respectively. Dr. Anthony Atala and Dr. Ali Khademhosseini, the most productive researchers in 3D bioprinting, may provide cooperation opportunities for interested researchers. Tissue Engineering Part A contributed the largest publication number, while Frontiers in Bioengineering and Biotechnology was the most attractive journal with the most potential. As for the keywords in 3D bioprinting, Bio-ink, Hydrogels (especially GelMA and Gelatin), Scaffold (especially decellularized extracellular matrix), extrusion-based bioprinting, tissue engineering, and in vitro models (organoids particularly) are research hotspots analyzed in the current study. Specifically, the research topics “new bio-ink investigation,” “modification of extrusion-based bioprinting for cell viability and vascularization,” “application of 3D bioprinting in organoids and in vitro model” and “research in personalized and regenerative medicine” were predicted to be hotspots for future research.